2020
DOI: 10.12820/rbafs.24e0098
|View full text |Cite
|
Sign up to set email alerts
|

Isolated and simultaneous perceived barriers to physical activity counseling

Abstract: The aim of this study was to determine the prevalence of perceived barriers and their isolated and simultaneous association with the practice of counseling for physical activity by primary health care workers. This is a cross-sectional study with 591 health workers, who work in the Family Health Teams. Counseling for physical activity was defined as the accomplishment of such a practice for more than six months. The barriers investigated were lack of time, lack of knowledge, lack of professionals to guide, lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…This demonstrates that numerous obstacles exist between clinicians' perceptions and patient action. There are several barriers to successful lifestyle change with counseling, these include lack of time, knowledge, forgetfulness, and orientation about patient compliance towards counseling [ 28 , 29 ]. Most of the patients also did not recall the counseling as well underutilized behavioral and lifestyle therapy for clinician counseling [ 30 , 31 ] Furthermore, while physicians may deliver counseling on certain lifestyle changes, they may not counsel all of their hypertensive patients on the same subject at every appointment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that numerous obstacles exist between clinicians' perceptions and patient action. There are several barriers to successful lifestyle change with counseling, these include lack of time, knowledge, forgetfulness, and orientation about patient compliance towards counseling [ 28 , 29 ]. Most of the patients also did not recall the counseling as well underutilized behavioral and lifestyle therapy for clinician counseling [ 30 , 31 ] Furthermore, while physicians may deliver counseling on certain lifestyle changes, they may not counsel all of their hypertensive patients on the same subject at every appointment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies support the use of the 5As model, little is known about the use of these strategies to advise physical activity applied in the context of PHC in the Sistema Único de Saúde (SUS) 13,[21][22][23] . A study carried out with professionals from the Expanded Center for Family Health and Primary Care (eNASF-AB) identified that the most reported counseling strategies were "advise", "assist" and "ask", with "arrange" being the least reported strategy [24][25][26][27][28] . However, it is necessary to understand how these strategies are used by the other professionals categories that make up the PHC.…”
Section: Introductionmentioning
confidence: 99%
“…Embora diversos estudos apoiem o uso do modelo 5As, pouco se sabe sobre o uso dessas estratégias para aconselhar atividade física aplicadas no contexto da APS no Sistema único de Saúde (SUS) 13,[21][22][23] . Estudo conduzido com profissionais da Equipe do Núcleo Ampliado de Saúde da Família e Atenção Básica (eNASF-AB) identificou que as estratégias de aconselhamento mais reportadas foram "aconselhar", "auxiliar" e "perguntar", sendo que "acompanhar" foi a estratégia menos reportada [24][25][26][27][28] . Porém é preciso entender como essas estratégias são utilizadas pelas demais categorias profissionais que compõem a APS.…”
Section: Introductionunclassified